FACTORS THAT AFFECT THE QUALITY OF FINANCIAL REPORTING AT BAITUL MAAL WAT TAMWIL (BMT) CENTRAL JAVA PROVINCE - Puja Nirma Rizki; Mohammad Ridwan; Andwiani Sinarasri (Jurnal Ilmiah Ekonomi Islam, 2026)
The quality of financial statements is a crucial indicator in assessing the accountability and performance of financial institutions, including Baitul Maal wat Tamwil (BMT). Factors such as Accounting Information Systems, Internal Control Systems, Financial Accounting Standards, and Accounting Understanding are considered to influence the quality of financial reporting. This study employed a quantitative approach using a random sampling technique, involving 126 BMTs in Central Java Province as research respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that Accounting Information Systems, Internal Control Systems, and the implementation of Financial Accounting Standards have a positive and significant effect on the quality of financial statements. Meanwhile, accounting understanding shows a positive but not significant effect. Simultaneously, the four variables explain 66.6% of the variance in financial statement quality, while the remaining percentage is influenced by other factors beyond the scope of this study. These findings highlight the importance of strengthening systems, internal controls, and compliance with accounting standards to improve the quality of financial reporting in BMT institutions.